Pendidikan Karakter dan Kewarganegaraan Sejak Dini: Sebuah Upaya Mengatasi Degradasi Moral di Era 4.0 - Zai, Krisdayanti; Marampa, Elieser R; Undras, Indraldo; Sinlae, Demsi Yanto (ANTHOR: Education and Learning Journal, 2023)
This writing is motivated by the phenomenon of immaturity and the inability to use technology properly which has a negative impact on the moral quality of humans themselves such as moral degradation, namely a decline or decrease in one's level of behavior. The emergence of cases of rape, murder, assault, brawls, and other bad acts shows that the current generation is still weak in morals. Therefore, this study aims to find a solution in dealing with moral degradation by instilling character education and civic values from an early age together. By using the research method of library research (library search) which analyzes, examines and explores it so that the correct steps are obtained in instilling the values of character education and citizenship. The results of this study indicate that character and citizenship education is an important alternative to overcome moral degradation which is declining due to the influence of the digital era 4.0 which includes religious values, honesty, tolerance, discipline, hard work, creative, independent, democratic, national spirit, love of the motherland, respect, achievement, communicative, peace-loving, and responsible.